Analisis Dampak Pencemaran Limbah Industri PT. S Terhadap Kehidupan Masyarakat di Kabupaten Sidoarjo - Adellia Mega Pratiwi; Wara Mustika Pudyaning Ratri; Muhammad Fiqih Samudera Wardhana; Naprillia Khusherawati; Shelvia Dwi Indriani; Annisa Qothrun Nada (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Environmental problems are increasingly showing a significant increase. Environmental problems are currently one of the most urgent problems to be resolved immediately from both the government and the surrounding community. Environmental pollution is formed from human activities that produce waste that enters the environment. Pollution by PT. S. Based on the data we researched for research using a qualitative descriptive research type method, this aims to describe a research phenomenon that was conducted in Sidoarjo Regency in March 2023. The establishment of a factory in a residential area causes environmental instability due to toxic waste and has not been fully processed to produce biota in the river around it is disrupted, besides that it is also exacerbated by a pungent and unpleasant odor that is often scattered. Waste disposal activities by PT. S. This unpleasant odor often wafts into their school so that learning activities become disrupted.